Rekonstruksi Status Hukum Dependent Contractor Pekerja Gig Economy: Upaya Mengisi Kekosongan Hukum Antara Mitra dan Pekerja - Allisya Destari Pratami (Advances In Education Journal, 2025)
This study addresses the legal gap in Indonesia's employment law, where the binary classification of workers versus partners fails to protect gig economy workers amid bogus self-employment, characterized by platform control without benefits like minimum wage or severance. The objective is to propose reconstructing the legal status of dependent contractors as a sui generis category to bridge this gap. Employing a normative juridical method, the research analyzes statutes (e.g., Employment Law No. 13/2003, Job Creation Law), comparative approaches from the UK (Uber v Aslam), Canada, and Spain, and conceptual frameworks on economic dependency versus subordination. Results reveal the obsolescence of current dichotomies, advocating criteria for dependent contractors: economic reliance (>80% income from one platform), lack of tariff control, and algorithmic subjection, granting partial rights like shared social security (BPJS), unionization, and unfair dismissal protection. This reconstruction enhances worker protection without stifling business flexibility, urging amendments to foster equitable digital economy growth